Unraveling the Molecular Mechanisms that Orchestrate Electron Transfer in Anaerobic Respiratory Metabolism of Shewanella oneidensis MR-1 - Neto, Sónia Estevão (2019)
"Among the portfolio of proposals for sustainable industrial processes, Microbial Electrochemical Technologies (METs) are emerging as a versatile option with multiple potential applications, such as bioremediation of metal contamination, wastewater treatment, and electricity production in microbial fuel cells (MFC). Such systems rely on microorganisms with the ability to transfer or receive electrons from electrodes, enabling the operation of these bioelectrochemical systems.(...)"